Glicerina bruta na alimentação de suínos. - Carvalho, Paulo Levi de Oliveira (2011)
Four experiments were carried out to determine the nutritional value and to evaluate performance of nursery piglets fed with two types of crude glycerine which were obtained from soybean oil (CGS), and mixture from animal fat + % soybean oil (CGA). In the Experiment I, a digestibility trial was carried out using 32 cross breed piglets (19.20 ± 1.52 kg), allotted in a completely randomized design in 2 × 3 factorial scheme (two different types of glycerine, and three levels of glycerine in the diet). The experimental unit consisted of one pig, with a total of four experimental units per diet. Glycerine levels used in the digestibility test were 4, 8, and 12% of the basal diet (corn + soybean based). The digestible (DE) and metabolizable energy (ME) values of glycerine were estimated by regression of DE and ME intake (kcal/kg) vs. glycerine intake (kg). The values (as-fed-basis) of DE and ME (kcal/kg) obtained were: CGS=5,070 and 4,556; CGA= 5,143 and 4,488, respectively. The results indicate that these two types of glycerine are highly available energy source for starting pigs feeding. In the Experiment II, 90 piglets (BW = 15.18±0.67 to 30.28±1.68 kg), were allotted in a completely randomized design in 2 x 4 factorial scheme, with of two types of crude glycerine (CGS and CGA) and four inclusion levels (3, 6, 9, and 12%). It was used five experimental (pens) unit with two pigs for each level of crude glycerine resulting in five replicates per treatment in the diet. Additionally it was formulated a control diet with no glycerine (0%). There were no interaction among levels of CG and types of crude glycerine, and the regression analysis indicates no effects (P≥0.05) of crude glycerine inclusion on performance and plasma variables. The results of performance suggest that it is feasible to use up to 12% of both CG on starting piglet diet, without impairing performance and plasma variables, besides providing a reduction of about 10% of the feeding cost. In the Experiment III, a digestibility trial was carried out using 32 cross breed pigs (45.08 ± 4.11 kg), allotted in a completely randomized design in 2 × 3 factorial scheme (two different types of glycerine, and three levels of glycerine in the diet). The experimental unit consisted of one pig, with a total of four experimental units per diet. Glycerine levels used in the digestibility test were 6, 12, and 18% of the basal diet (corn + soybean based). The digestible (DE) and metabolizable energy (ME) values of glycerine were estimated by regression of DE and ME intake (kcal/kg) vs. glycerine intake (kg). Overall, the values (as-fed-basis) of DE and ME (kcal/kg) obtained were: CGS= 5,040 and 4,481; CGA= 5,234 and 4,707, respectively. The results indicate that these two types of glycerine are highly available energy source for growing finishing pigs feeding. In the Experiment IV, there were involved 63 piglets (BW = 30.53 to 59.55 kg) in the growing phase and (BW = 60.35 to 89.91 kg) in the finishing phase, which were allotted in a completely randomized design in 2 x 4 factorial scheme, with two types of crude glycerine (CGS and CGA) and four levels (3, 6, 9, and 12%), resulting in seven replicates per treatment and one pigs for each level of crude glycerine. Additionally it was formulated a control diet with no glycerine (0%). There were no interaction (P≥0.05) among levels of CG and types of glycerine sources, and the regression analysis indicates no effects (P≥0.05) of crude glycerine inclusion on performance and carcass traits (backfat thickness and loin depth). The results of performance suggest that it is feasible to use up to 12% of both CG on of growing finishing pigs diet, without impairing performance and carcass traits, besides providing a reduction of about 9% of the feeding cost. In the Experiment V, at the end of the finishing phase, pigs were slaughtered to determine the quantitative and qualitative traits of the carcass. For plasma variables there were no interaction (P≥0.05) between levels of CG and types of glycerine sources, and the regression analysis indicates no effects (P≥0.05) of crude glycerine inclusion on carcass traits. For qualitative of carcass traits, the pH24 variable was linearly reduced (P≥0.05) for CGS and DRIP variable was quadratic response (P≥0.05) for CGA. The results suggest that it is feasible to use up to 12% of both CG obtained from soybean oil and mixture) on pigs diet, without impairing the quantitative traits of the carcass and meat quality.